2011
DOI: 10.1177/193229681100500231
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Hyperglycemia and Postoperative Infection after Lower Limb Arthroplasty

Abstract: Abbreviations: (ASAPS) American Society of Anesthesiologists physical status, (BG) blood glucose, (BMI) body mass index, (BUN) blood urea nitrogen, (DM) diabetes mellitus, (I&D) irrigation and debridement, (INR) international standardized ratio, (MI) myocardial infarction, (PJI) periprosthetic joint infection, (POD) postoperative day

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
157
3
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(174 citation statements)
references
References 26 publications
5
157
3
9
Order By: Relevance
“…A previous study found an association between HbA 1c levels C 8 and wound complications but no association with early postoperative deep infection in patients with DM after TKA [6]. On the other hand, our finding of the only association of preoperative FBG C 200 mg/dL with superficial surgical site infection is in contrast with previous studies reporting the association of preoperative FBG level C 126 mg/dL [9], postoperative FBG level C 126 mg/dL [21], and postoperative FBG level C 200 mg/dL [16] with the occurrence of complications after total joint arthroplasty. Our findings, taken together with previous studies, suggest that surgeons should think carefully before performing this elective procedure in a patient with HbA 1C C 8 or FBG C 200 mg.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A previous study found an association between HbA 1c levels C 8 and wound complications but no association with early postoperative deep infection in patients with DM after TKA [6]. On the other hand, our finding of the only association of preoperative FBG C 200 mg/dL with superficial surgical site infection is in contrast with previous studies reporting the association of preoperative FBG level C 126 mg/dL [9], postoperative FBG level C 126 mg/dL [21], and postoperative FBG level C 200 mg/dL [16] with the occurrence of complications after total joint arthroplasty. Our findings, taken together with previous studies, suggest that surgeons should think carefully before performing this elective procedure in a patient with HbA 1C C 8 or FBG C 200 mg.…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, achieving optimal glycemic control in patients with DM is important. However, evidence for which glycemic markers are most predictive of complications is less clear [1,6,7,9,16,21]. We wanted to determine the correlations among the four commonly used glycemic markers and to identify the glycemic markers that were most strongly associated with the occurrence of surgical site infections and postoperative wound complications in patients with DM after undergoing TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, not only is the preoperative glucose level an important factor, but Mraovic et al demonstrated that the postoperative blood glucose level also plays an important role as far as the risk for PJI is concerned (28). The authors stated that patients with sugar levels of greater than 200 mg/dl on postoperative day one were twice more likely to develop PJI.…”
Section: Medical Optimization Of Hostmentioning
confidence: 99%
“…Mraovic et al, reviewed elective primary total hip and knee arthroplasty from 2000 to 2008. They found that Non-DM patients were 3 times more likely to develop the infection if their morning BG was >140 mg/dl on post-operative day and gave their concluding remarks that even patients without a diagnosis of DM who developed postoperative hyperglycemia had a significantly increased risk for the infection [26].…”
Section: Arthroplasty and Non-diabetic Hyperglycemiamentioning
confidence: 99%